Laser as a promising non-invasive technique to treat oral submucous fibrosis: A systematic review of the literature - Sonia Gupta (Elsevier, 2021)
Background: Oral submucous fibrosis (OSMF) is one of the common oral potentially malignant disorders that can result in severe morbidity. Depending upon the stage of disease, multiple management therapies exist which include medicinal and surgical approaches. Although the surgical approach is preferred in severe conditions, numerous studies have reported its post-surgical deteriorating outcomes including increased fibrotic changes. To reduce these post-surgical complications, Light amplification by stimulated emission of radiation (Laser) has been introduced and studied as a non-invasive technique to treat oral submucous fibrosis. However, there exists a lack of knowledge about ‘which laser shows a better post-treatment outcome’. Accordingly, this review aims to answer this question. Materials and methods: A systematic review of the published literature was performed using an electronic search in PubMed/Medline, Science Direct, Web of Science, Embase, J- STAGE, Google Scholar, and Scopus databases, from 1952 till 2019 using keywords like, ‘Oral submucous fibrosis’, ‘Treatment’, ‘Laser’, ‘Trismus’, ‘ Fibrosis’, ‘Surgical’, ‘Non-invasive’, and ‘Postoperative results’. Results: The search strategy revealed 20 relevant published studies in which laser had been used to treat 250 patients of OSMF. Effective results were found without any complications in all the cases after follow up. Conclusion: Observing the current literature, it can be concluded that laser might be used as a potential non-invasive approach in the management of OSMF, however, large scale studies are required to investigate the efficacy and other effects of this technology.